Immigration in the spanish press.empirical and methodological findings in conecction with the news framework theory - Igartua, Juan José; Muñiz, Carlos; Cheng, Lifen (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2014)
The present research has analyzed the positioning of the national press with regard to the immigration issue. We have analyzed 819 news stories that had immigrants as protagonists or immigration as an issue and that were published in the following newspapers El País, El Mundo, ABC and La Razón. We elaborated the News Frames Scale to evaluate quantitatively the news stories about immigration. For the identification of the news frames about immigration (defined as latent constructs) we performed techniques of multivariate analysis, such as factor analysis and discriminant analysis. Thus, 17 types of news frames about immigration have been identified. We have also verified that the treatment of immigration depends to a great extent on the publishing line of the newspaper that publishes the news story (conservative or progressive) and on its model of newspaper (prestige press or popular sensationalist).
Keywords: News frames; Agenda-Setting; Frame theory; Immigration; Content analysis